Subjects for Which Various Ministries and Departments of the Government of India are Responsible - Parliament Secretariat (Parliament Secretariat, 1950)
The document on the Government of India’s responsibilities (as of July 31, 1951) provides a comprehensive overview of the roles and functions of various ministries and departments. It details the key areas of governance, including commerce, industry, communications, defense, education, finance, health, home affairs, labor, law, scientific research, railways, transport, rehabilitation, and civil works. The Planning Commission’s role in resource assessment and development planning is also highlighted. This structured outline ensures clarity in administrative duties, fosters accountability, and serves as a reference for efficient governance and policy-making across central government bodies.
Parliament Secretariat New Delhi
Keywords: Government Of India; Ministries; Responsibilities; Administration; Planning Commission; Finance; Education; Health; Defence; Agriculture